Quality Management Practices and Performance Measurement in the Manufacturing Industry: An Instrument Validation = Amalan Pengurusan Kualiti dan Pengukuran Prestasi dalam Industri Pembuatan: Suatu Pengesahan Alat - Zaharuzaman, Jamaluddin; Ahmad Mahir, Razali; Zainol, Mustafa; M. R., Abdul Hamid (Universiti Kebangsaan Malaysia, 2016)
The aim of this article was to validate an instrument of quality management practices (QMPs) and performance measurement for the manufacturing industry in Malaysia. QMPs and performance were measured using the following six value indicators: Management commitment, training, process management, quality tools, continuous improvement and organisational performance. A total of 480 questionnaires were distributed and 210 questionnaires were valid for analysis. A confirmatory factor analysis (CFA) approach was employed using analysis of moment structures (AMOS) software. The results for the hypothesised CFA model showed the following fit statistics: Comparative fit index (CFI) = 0.924, Tucker Lewis index (TLI) = 0.913 and root mean square error of approximation (RMSEA) = 0.061. The values of CFI and TLI≥ 0.9 and at the same time the value of RMSEA ≤ 0.08 showed that CFA model fits the data very well. Hence, the results of the study can be used by managers in manufacturing companies to consider and adapt their QMPs and performance assessments toward increasing competitiveness.